Competency of Public Managers in Majlis Bandaraya Melaka Bersejarah (MBMB) / Khairiyah Nor Sarah Rusli and Nur Syuhaidah Roslan - Rusli, Khairiyah Nor Sarah; Roslan, Nur Syuhaidah (Faculty of Administrative Science and Policy Studies, 2012)
Public managers are the people who hold the responsibility to serve public interest and their demands. In order to meet the needs of the local community, public managers need to render effective and efficient services. The recent concern regarding poor job performance by certain senior or executive public officials in public sector has rise questions regarding their competencies. Based on this issue, this study was conducted to identify whether the public managers in Majlis Bandaraya Melaka Bersejarah (MBMB) possessed the relevant competencies to perform their duties as public managers. This study focused on the public managers in MBMB who hold degree and above in their education background. A sample of 42 public managers from 14 different departments has been selected as a respondent for this study. The main objectives of this study were to evaluate the competency level of MBMB’s managers, to measure the technical, ethical and leadership competency of MBMB’s managers and to determine the additional attributes that enhances the managers’ competency. The statistical techniques used in this study are Descriptive Statistics and Correlation Analysis. This study has proved that most of the public managers in MBMB possessed the high level of competency in performing their daily duties as public manager. Besides, the findings have shown that there is significant high positive relationship between technical, ethical and leadership competencies to the level of public managers’ competency. In addition, most of public managers agreed that the additional attribute that enhance competency which are creativity, innovation and entrepreneurship competencies also will led to high level of managers’ competency.